Does Toxic Leadership, Employee Welfare, Job Insecurity, and Work Incivility Have an Impact On Employee Innovative Performance at Private Universities in LLDIKTI III Area? - Ramaditya, Muhammad; Effendi, Syahrul; Syahrani, Nabilla Ayu (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
This study aims to determine the impact of toxic leadership, workplace incivility, employee welfare and job insecurity on employee innovative performance in private universities in the LLDIKTI III area. This study used causal and associative approach, where data is obtained from the results of collection using a questionnaire. The population in this study were lecturers from Private universities in the LLDIKTI III area. The sample in this study were 376 respondents. The analysis tool used is SmartPLS 3 with Structural Equation Modeling technique based on Partial Least Square. The results of this study state that Employee Welfare affects Employee Innovative Performance. Then Toxic Leadership and Employee Welfare affect Workplace Incivility, and Toxic leadership, Workplace Incivility and Employee Welfare affect Job Insecurity at private university. Leaders who have a Toxic Leadership, work incivility will not have a good impact on Employee Innovative Performance, while also reducing the innovative performance of employees. Leaders can pay more attention to welfare and insecurity to boost innovative performance. Keywords: employee welfare, innovative performance, job insecurity, toxic leadership, workplace incivility